CRITICAL THINKING AND PROBLEM SOLVING INTRODUCE TEACHERS AND STUDENTS TO DEEP LEARNING AND BECOME LIMITLESS HUMAN - Setiawan, Iwan (Universitas Muhammadiyah Semarang, 2018)
Teaching is a very noble profession. Various professions and experts in the world are taught byteachers. They do not only teach knowledge they master, but teachers also teach various things onhow to address this life, which is not only life in the world, but also life in the Hereafter.Moreover, teachers do not only teach how to master certain knowledge, but they also teach howthe acquired knowledge can be beneficial, not just for themselves, but for other people even forthe universe.Therefore, teachers are not only required to master a particular subject, but they alsohave to master and understand everything about human beings, such as characters, social,psychology, human relationships, wishes and wishes.Teachers have to be able to provide so muchtime even if they can take extra time from their available time. Besides having to prepare to teachand deliver lessons in the classroom, teachers are also required to think about how to organizeand condition their pre-teaching classes, in which the classes consist of a group of people withdifferent cultural backgrounds, economy, family conditions, characters and attitude, emotion,psychology, and so on. Teachers do not only focus on teaching one student, but they also have tothink of tens, hundreds and maybe thousands of diverse and heterogenous students.Nevertheless,a phenomenon that has happened lately is that many teachers who become victims of violenceeither from the sidewa or oaring old students. The handling of students who teachers mayunderstand correctly how to handle the students’ characters, nature and extent of offensescommitted by the students, is sometimes regarded as a cruelty and a lack of merit. There may besome unscrupulous teachers who are unable to maintain and condition their emotion whendealing with students, but we do not then generalize any problem of handling students in whichthe element of assertiveness is considered violent.Although teachers have tried their best toeducate and nurture their students to become human beings who have good characters, pleasenote that these students come from different and diverse backgrounds that make up differentcharacters. Teachers should be able to cultivate the spirit of learning and teaching a good moral tostudents born from families living in harsh environments, slums, minimal educationalenvironment. In fact, not a few students who live in a 2m x 2m house inhabited by 5-6 people ofa family, they have to live their lives in the house, cooking, sleeping, washing all done in thatplace. Even in order to sleep alone, they have to take turns like people who do a night watch. Ifyou look at these conditions, we will face students who have never studied at home, sleeping in the classroom when learning because of lack of sleep, appeared character of thuggery because ofthe family economic problems and harsh environment.Teachers are very hard to think about howto provide the best education for the students who could be his child even less he noticed for thesake of his students.